2022
DOI: 10.1002/jctb.7285
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of CaS preparation from lignite‐reduced phosphogypsum in a fluidized bed

Abstract: BACKGROUND: Phosphogypsum (PG) is a solid waste. For a fluidized bed, current research has focused on the preparation of CaO and SO 2 by PG decomposition, while less research has been conducted with calcium sulfide (CaS) as the target product. Therefore, the effect of different conditions on the preparation of CaS by coal reduction of PG was investigated in a fluidized bed. The mechanism of the reaction between coal and PG was revealed through experiments and kinetic calculations.RESULTS: PG decomposition is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This is mainly because when the C/S molar ratio is to the sulfide residues in the slag, thereby reducing the desulfurization rate of the system. 51,52 In summary, it can be concluded that the amount of reducing agent and smelting temperature are the key factors affecting the desulfurization effect and slag phase structure in the new process of acid-making and slag wool production based on phosphogypsum. It was appropriate to add the reductant with a C/S molar ratio of 0.5−0.8, which was consistent with the previous research results.…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly because when the C/S molar ratio is to the sulfide residues in the slag, thereby reducing the desulfurization rate of the system. 51,52 In summary, it can be concluded that the amount of reducing agent and smelting temperature are the key factors affecting the desulfurization effect and slag phase structure in the new process of acid-making and slag wool production based on phosphogypsum. It was appropriate to add the reductant with a C/S molar ratio of 0.5−0.8, which was consistent with the previous research results.…”
Section: Resultsmentioning
confidence: 99%
“…The work [ 13 ] proposed a simple and efficient approach for the high-purity CaSO 4 ·2H 2 O (DH) whiskers and α-CaSO 4 ·0.5H 2 O (α-HH) whiskers derived from phosphogypsum (PG). The work [ 14 ] studied the effect of different conditions on the preparation of CaS by reducing PG with coal in a fluidized bed. This method not only requires a large initial investment, but also forms new pollutants and faces environmental pollution problems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared with traditional limestone calcination, CO 2 emissions are significantly reduced. While CaSO 4 decomposes at temperatures of up to 1400 °C, introducing reducing agents can drastically lower this temperature 6 . Common reducing agents mainly include carbon‐based (lignite, 7 anthracite, 8 coke, 9 coal gangue, 10 CO 11 ) and sulfur‐based (sulfur, 12 pyrite, 13 H 2 S 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…While CaSO 4 decomposes at temperatures of up to 1400 °C, introducing reducing agents can drastically lower this temperature. 6 Common reducing agents mainly include carbon-based (lignite, 7 anthracite, 8 coke, 9 coal gangue, 10 CO 11 ) and sulfur-based (sulfur, 12 pyrite, 13 H 2 S 14 ). Therefore, the conversion of CaSO 4 to CaO is completely feasible in terms of process.…”
Section: Introductionmentioning
confidence: 99%